Conocimiento sobre investigacin cientfica y actitudes hacia la investigacin en estudiantes de pregrado de una universidad pblica, Trujillo - 2022 - Grados Tellez, Emely Yanira (2022)
This study was carried out with the objective of determining the relationship between knowledge about scientific research and attitudes towards research in students of the IX undergraduate cycle of secondary education specialty in History and Geography, 2022. The population and the sample were made up of 18 students. between men and women, so it was not necessary to apply a sampling. This research was carried out under a quantitative, theoretical and correlational approach, with a non-experimental design. The instruments used were a questionnaire for the first variable and an attitude scale for the second variable. The results showed that knowledge about scientific research and attitudes towards research are significantly related (sig. = 0) with a Pearson correlation of 0.260, so there is a low and direct relationship between the variables, indicating that the greater the knowledge about scientific research in students, better their attitudes towards research.